2000
DOI: 10.1111/j.1745-4603.2000.tb00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Properties of White Fresh Cheese Filled With Sodium Caseinate

Abstract: The yield, moisture loss and viscoelastic properties of white fresh cheeses containing sodium caseinate were determined and compared to those of a reference cheese without sodium caseinate. Added sodium caseinate resulted in higher cheese yields and lower moisture losses during aging. Creep compliance tests were performed on the cheeses using a parallel plate viscoelastometer.Multiple regression analysis of the experimental data providedprst order models that explain the variation of most of the viscoelastic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…The creep assay, to study the effects of formulation changes on the properties of Queso Blanco, was reported by Lobato-Calleros, Aguirre-Mandujan, Vernon-Carter, and Sánchez-García (2000), resulting very useful for characterizing the different cheese formulations.…”
Section: Food Engineering Materialsmentioning
confidence: 99%
“…The creep assay, to study the effects of formulation changes on the properties of Queso Blanco, was reported by Lobato-Calleros, Aguirre-Mandujan, Vernon-Carter, and Sánchez-García (2000), resulting very useful for characterizing the different cheese formulations.…”
Section: Food Engineering Materialsmentioning
confidence: 99%
“…Storage temperature is one of the main factors affecting shelf-life and can cause some alterations resulting in the product unacceptability (Labuza, 1982;Singh, 1994). Several studies have been carried out to monitor fresh cheese shelf-life by using chemical indices and/or innovative techniques (Wells, 1998;Lobato-Calleros & Aguirre-Mandujano, 2000;Riva & Giangiacomo, 2001;Toppino, Riva, Cigoli, & Civardi, 2002;Toppino & Riva, 2003). Among these studies, some of them have been carried out on Crescenza cheese, which covers more than 40% of the Italian fresh cheese market.…”
Section: Introductionmentioning
confidence: 97%
“…The use of fat replacers decreased the chewiness characteristics by loose the compact and dense protein matrix characteristics. 29,34 Koca & Metin 29 found out that the low-fat fresh Kashar cheeses produced by using fat replacers (SimplessesD-100 and Raftiline ® HP) were softer and less chewy. This result could be explained by activity of polar groups in fat mimetics resulting in increase in cheese moisture content and consequently improving the low-fat cheese texture.…”
Section: Resultsmentioning
confidence: 99%